Las revistas juveniles en la formación de adolescentes de bachillerato general unificado - Cástula Carolina, Reyes Herrera (2016)
The actual degree job report meets the results reached by the author about “The youthful magazines in the unified general secondary school teenagers’ formation”, from setting out the problems situation around the questioning concerning the content that should be published in a magazine directed to teenagers; the elements to keep in mind to promote the written media’s reading, and the way in which it has influence in the content of a student formation’s magazine; considering, particularly the magazines Cosmopolitan and Generation 21, and delimiting the study to the unified general secondary school’s students of the Treasury Missionary Educational Unit “Santa María Mazzarello”. In the investigative process’s development, it was systematized the theory about communication and the magazines as media, considered the topic’s theoretical support, and it were also applied different investigative methods, from the analysis-synthesis; the process of induction-deduction and some of those of empiric characters; such as, the poll, the interview, and the documental study, which promoted to diagnostic the real status of the problem and its corroboration……